IMPLEMENTASI PEMBIAYAAN MURABAHAH (STUDI KASUS WARUNG MIKRO BANK SYARIAH MANDIRI CABANG BOJONEGORO ) - arifin, bakhtiyar; warsidi, warsidi (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
One of the segmentation of Bank Syariah Mandiri to distribute financing to micro segment is that the warung micro aims to provide convenience to the micro enterprise in obtaining additional capital to expand its business, although it does not close to provide financing to customer who does note have micro enterprises.This research uses qualitative research to know how the implementation of Murabahah financing on sharia bank independent of warung micro segment in practice and theory. Is the murabahah contract that is used in accordance with the fatwa of The National Sharia Council Indonesia Counsil of Religious Scholars in meeting the needs of the cusmoter to increase working capital.The finding in the field that the contract used was a hybrid contract between murabahah and wakalah contract. So that presence of warung mikro bank syariah mandiri felt very beneficial to the customers in gaining capital increase for its business development easy and sharia. The result of this study concluded that the contract and process carried out by the Warung Mikro Bank Syariah Mandiri Bojonegoro already in accordance with the applicable regulations in Indonesia is in accordance with the fatwa of the National Sharia Council Indonesia Counsil of Religious Scholars No. 04/DSN-MUI/IV/2000 on the financing of Murabahah ang implementation of murabahah financing. It is reflected in the filing process until the agreement between the bank and the customer.Keywords: Murabahah, Warung Mikro Bank Syariah mandiri, Murabahah Working Capital.